Analysis of learning outcomes of a foreign language in adults with a distance education method - Ríos González, Rosa María (2021)
Nowadays, the importance of learning a foreign language has increased, so, not only young students need to study a foreign language for being well prepared to face their challenges, but also adult pupil. For them, it is important to be prepared and the teacher's job is to guide them and to support them. For this, we try to find the skills and attitudes needed by adult learners a foreign language and the challenge that it represents for them.